2018
DOI: 10.1016/j.chemosphere.2018.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Vertical up-flow constructed wetlands exhibited efficient antibiotic removal but induced antibiotic resistance genes in effluent

Abstract: The intensive use of antibiotics results in their continuous release into the environment and the subsequent widespread dissemination of antibiotic resistance genes (ARGs), thus posing potential risks for public health. Although vertical up-flow constructed wetlands (VUF-CWs) have been widely used to treat wastewater in remote or rural regions, few studies have assessed the potential risks of ARG dissemination when VUF-CWs are applied to treat wastewaters containing antibiotics. In this study, the removal perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(24 citation statements)
references
References 33 publications
0
23
1
Order By: Relevance
“…The reports available in the literature suggest that, just like conventional WWTPs, CWs could be considered as hotspots for the spread of antibiotic resistance in the environment. Song et al [ 69 ] evaluated the fate of ARGs ( sul and tet ) in three lab-scale vertical flow CWs. They found out a positive correlation between abundances of ARGs and the accumulation of SMX and tetracyclines in different layers of CW substrate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reports available in the literature suggest that, just like conventional WWTPs, CWs could be considered as hotspots for the spread of antibiotic resistance in the environment. Song et al [ 69 ] evaluated the fate of ARGs ( sul and tet ) in three lab-scale vertical flow CWs. They found out a positive correlation between abundances of ARGs and the accumulation of SMX and tetracyclines in different layers of CW substrate.…”
Section: Resultsmentioning
confidence: 99%
“…Although the effluent had lower abundances of ARGs than that in the wetland media, the occurrence of ARGs in effluent might still pose risk for public health. Moreover, the relative abundances of sul and tet genes showed a significant increase in all samples during the SMX and tetracycline treatment period [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the removal of DCF was not affected by aeration (removal 50%) (Sochacki, Felis, Bajkacz, Nowrotek, & Miksch, 2018). On the other hand, vertical up-flow CWs exhibited efficient antibiotic (SMX and tetracycline) removal efficiencies (>98%); however, the exposure of antibiotics resulted in harboring abundant ARGs (Song et al, 2018). Similarly, removal of antibiotics (SMX) from ANNUAL LITERATURE REVIEW saline wastewater in CW mesocosms and CW microcosms was evaluated to test the influences of various salinity levels on SMX removal and it was revealed that high salinity level (EC at 30 mS/cm) significantly (p < .05) suppressed SMX removal in CW microcosms (Liang et al, 2018).…”
Section: Wetlands For Emerging Pollutant Removalmentioning
confidence: 94%
“…Moreover, He, Nurul, et al (2018) reported that the removal of ARGs was higher (in the range of 14% [Intl1] to 95% [sul2]) in a CW. In contrast, Song et al (2018) used a VFCW to remove the ARGs, which resulted in a significant increase in sul and tet genes with operating time and with significant correlations between 16S rRNA and ARG copy numbers in the effluent.…”
Section: Annual Literature Reviewmentioning
confidence: 99%
“…Other considerations are necessary to apply these systems to remove antibiotics to reduce the supports' adsorption process. The long residence time of antibiotics or metals subjected to heterogeneous conditions within the CWs, along with the presence of other stressors, can also promote the microorganism's antibiotic resistance by selective pressure [117,118]. Zhang et al (2020) reported about the increase of sulfonamide resistance genes, as well as the increase of sulfamethoxazole concentration in the lower and the medium layers of the CWs [119].…”
Section: Constructed Wetlandsmentioning
confidence: 99%